2010
DOI: 10.1038/sj.bjc.6605569
|View full text |Cite
|
Sign up to set email alerts
|

Study of matrix metalloproteinases and their inhibitors in prostate cancer

Abstract: BACKGROUND: Extracellular matrix metalloproteases (MMPs) have raised an extraordinary interest in cancer research because of their potential role in basal membrane and extracellular matrix degradation, consequently facilitating tumour invasion and metastases development. METHODS: An immunohistochemical study was performed using tissue arrays and specific antibodies against MMPs 1, 2, 7, 9, 11, 13, 14, and their tissue inhibitors, TIMPs 1, 2 and 3. More than 2600 determinations on cancer specimens from 133 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 48 publications
(54 reference statements)
5
51
0
2
Order By: Relevance
“…25) Conversely, knocking down MMP-2 and MMP-9 genes was found to decrease tumor invasion, migration, metastasis, and angiogenesis in glioblastoma and prostate cancer cells. [26][27][28][29] TIMPs inhibit the activity of MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…25) Conversely, knocking down MMP-2 and MMP-9 genes was found to decrease tumor invasion, migration, metastasis, and angiogenesis in glioblastoma and prostate cancer cells. [26][27][28][29] TIMPs inhibit the activity of MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…An association between MMPs and/or TIMPs expression and parameters indicative of prostate cancer aggressiveness has also been reported. Recently, Escaff et al [ 56 ] reported that MMPs/TIMPs expressions are in general higher in prostate cancer than in prostate benign tissue, confi rming the important role of these factors in the molecular biology of prostate cancer.…”
Section: Mmpsmentioning
confidence: 99%
“…In the same manner, BREHMER et al (2003), ZHONG et al (2008 observed higher expression of MMP-2 and MMP-9 in neoplastic human prostate than in normal ones or with BPH, respectively. Besides, ESCAFF et al (2010) found higher expression of different types of MMP and TIMP in human prostates with carcinoma than in glands with benign changes, concluding that such enzymes have an important role in the molecular biology of prostatic carcinomas.…”
Section: ----------------------------------------------Types Of Pia--mentioning
confidence: 88%